From bad to worse: The economic impact of COVID-19 in developing countries: Evidence from Venezuela - German Caruso; Lautaro Chittaro; Maria Emilia Cucagna; Luis Pedro Espana (Latin American Economic Review, 2021)
Policy responses to COVID-19 affected the dynamic of economic growth and labor markets worldwide, hitting economically harder on developing countries. These policies involved economic lockdowns that included the shutdown of the main statistical exercises, making it almost impossible to assess the breadth and variety of their effects. Using a phone survey, this paper examines the impact of the quarantine implemented in Venezuela on labor market outcomes. The identification strategy exploits the exogenous variation in the severity of the lockdown in different regions of the country. The main result indicates a 16.5 percentage points reduction in employment, while in regions with severe lockdowns the reduction has been 13.8 p.p. larger. In particular, the self-employed and informally employed were hard hit by the lockdown. To cope with this effect, households sold their productive assets, reduced their savings, sought for alternative income sources and looked for help from relatives. This paper does not find a differential effect on the number of COVID-19 cases in more severe lockdown settings. Results are robust to endogenous migration and alternative specifications.
Keywords: D31; I00; J13; 330; COVID-19; Economic impact; Developing countries; Venezuela